Global strategies for cervical cancer prevention. Issue 1 (February 2016) - Pimple, Sharmila; Mishra, Gauravi; Shastri, Surendra
Abstract : Purpose of review: Cervical cancer still remains the fourth most common cancer, affecting women worldwide with large geographic variations in cervical cancer incidence and mortality rates. There exist vast disparities in cervix cancer control and prevention efforts globally. The present review addresses the current developments in cervical cancer prevention and control across both high-income countries and low–middle income countries and attempts to identify new strategies that might help address the gaps in cervical cancer care disparities globally. Recent findings: Paradigms for cervix cancer screening are changing in high-resource settings from cytology-based screening to adoption of molecular screening and cotesting to achieve program effectiveness. Low–middle income countries with larger burden of cervical cancer continue to face financial and logistic limitations to make both cervix cancer screening and human papillomavirus vaccine available to their populations. Alternative low-cost screening technologies, operationally feasible implementation strategies, reduction of cost of procurement and delivery approaches for human papillomavirus vaccine need assessment to decrease cancer care disparities. Summary: Efforts directed toward cervix cancer prevention and early detection for improvements in cervical cancer outcomes of incidence and mortality have to be proportionately matched by access to acceptable standards of cancer care.